Concept of God in the discourses of Al-Ghazālī (d. 1111) and Maimonides (d. 1204) / Nurhanisah Senin - Nurhanisah, Senin (2016)
Despite the fact that Islam and Judaism are both monotheistic religions, they embrace dissimilar concepts of unity. The differences entail the emergence of theological and philosophical discourses among Muslim and Jewish scholars. Arguments on God’s unity, incorporeality and His relation to creation thus result in debates on God’s existence, attributes and actions. Hence, as part of bridging interfaith dialogue between Islam and Judaism, this study aims to provide a comparative analysis of al-Ghazālī and Maimonides, both of whom were considered the principal spokespersons in their respective religions in the 11th and 12th centuries. Historical and textual analyses along with the comparative method are employed to examine their treatises. Al-Ghazālī’s discussion on God was elaborated in Iḥyā’ ‘Ulūm al-Dīn (The Revival of Religious Sciences) and Al-Iqtiṣād fī al-I’tiqād (Moderation in Belief). Maimonides extensively discussed God in Dalālat al-Hāi’rīn (The Guide of the Perplexed) and Mishneh Torah (The Repetition of Torah). The data from these texts was compared directly without referring to any theoretical stance such as kalām or philosophy, since the two scholars had different methods of argumenting. If kalām was employed in analyzing both arguments, it will be unjust towards Maimonides. On the other hand, if philosophy was employed, it will be unjust towards al-Ghazālī. This study finds that both al-Ghazālī and Maimonides believed that God possesses a necessary existence, but they contrasted in their underlying arguments where al-Ghazālī only affirmed God to be the necessary existent. Maimonides advocated a dualistic approach to necessary existence. They both believed that the universe was created, but Maimonides additionally affirmed that it was created from eternal matter. Both scholars acknowledged God’s will and particularization, but al-Ghazālī believed it transcends every occurrence while Maimonides only related it to the arbitrariness of the spheres and supported necessary causation in explaining contingencies. Al-Ghazālī asserted that God possesses attributes, while Maimonides absolutely refuted subscribing attributes to God’s Essence. Finally, al-Ghazālī held that God’s will transcend His actions, whereas Maimonides subscribed to both will and providence in perceiving His actions. Apparently, their differences stem from their stances on incorporating philosophical arguments. In sum, it is observed that al-Ghazālī acknowledged God as the Agent of Will, while Maimonides perceived God within the conception of the Intellect, Intelligen and Intelligible.